Analisis Kesalahan Berbahasa dalam Tataran Semantik pada Film “5 Menara” Karya Ahmad Fuadi - Rita Rismawati; Silvi Sri Hildayanti; Risma Destriani; Ai Siti Nurjamilah (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
This study aims to analyze language errors at the semantic level in the film Negeri 5 Menara "Man Jadda Wajada" by Ahmad Fuadi. In this film, language is used as a medium to convey moral messages related to education and life motivation. However, there are several language errors that affect the clarity of the meaning communicated to the audience. This research employs a qualitative descriptive method with semantic analysis, focusing on errors in word usage, both denotative and connotative meanings. Data were collected through observation of the dialogues in the film, which were then analyzed based on the semantic errors found. The results show that there are 20 language errors, including inappropriate word choices, ambiguous sentence structures, and the use of non-standard words. The correction of these errors is expected to improve communication clarity in the film and contribute to a deeper understanding of the application of proper language norms in audiovisual works. This study is expected to provide theoretical contributions to the analysis of language errors in semantics and enhance the quality of communication in film media.